The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.pscychresns.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI markers support a model of small vessel ischemia for depressive symptoms in very old adults

Abstract: In older adults, depressive symptoms are associated with lower quality of life, high morbidity and mortality. This study aims to identify brain magnetic resonance imaging (MRI) features associated with late-life depressive symptoms in the population. Older community-dwelling adults (n = 314) from the Health ABC study underwent brain MRI. Logistic regression was used to characterize the relationships between depressive symptoms (Center for Epidemiologic Studies of Depression scale, CES-D) and the following whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 40 publications
(42 reference statements)
3
33
3
1
Order By: Relevance
“…In very old adults with depression, loss of grey matter volume was most significant in the bilateral insula and anterior cerebral cortex, supporting a cerebrovascular pattern of LLD [133]. These changes, together with WMHs, are associated with both depression and cognitive decline and may precede the incidence of both disorders in elders by 10 years [134], suggesting an etiological pathway from ischemia to increased depressive burden [133].…”
Section: Resultsmentioning
confidence: 99%
“…In very old adults with depression, loss of grey matter volume was most significant in the bilateral insula and anterior cerebral cortex, supporting a cerebrovascular pattern of LLD [133]. These changes, together with WMHs, are associated with both depression and cognitive decline and may precede the incidence of both disorders in elders by 10 years [134], suggesting an etiological pathway from ischemia to increased depressive burden [133].…”
Section: Resultsmentioning
confidence: 99%
“…However interpreting these findings requires considering other evidence which demonstrates that periventricular, deep brain, and overall WMH are all highly correlated, and that an arbitrary, categorical distinction between periventricular and deep brain WMHs is not empirically supported (75); this study suggests WMHs extended smoothly out from the ventricles as a function of increasing overall burden. Consistent with these observations, a recent population-based study demonstrated that depression was associated with WMH accumulation around the ventricles (76), and another recent study found the ratio of WMH to non-WMH tissue differed between depressed patients and controls only in the upper cingulum (77). …”
Section: The Relevance Of Wmh Extent and Localizationmentioning
confidence: 58%
“…Voxel-based research similarly suggests LLD is associated with lower FA across multiple white matter tracts including those implicated in cognitive and affective processing (76, 79). Network based analysis of DTI data suggests LLD is associated with reduced connectivity of temporal regions (80).…”
Section: Tract Specific and Whole-brain White Matter Microstructural mentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we used a group of older adults enrolled in a study of late-life depression (LLD). As depression in older adults is associated with the presence of small vessel ischemic disease (Alexopoulos, 2006; Taylor et al, 2013; Tudorascu et al, 2014) this group is likely to have a significant burden of WMH, and thus is well-suited for testing how WMH burden interfere with tissue segmentation and registration. In general, aging populations tend to have higher WMH burden, but patients with LLD often have an even higher WMH burden compared to age-matched healthy controls (Herrmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%